India Basin Waterfront Park, San Francisco. - GONCHAR, JOANN (Architectural Record, 2025)
The article focuses on the development of India Basin Waterfront Park in San Francisco, which aims to prioritize community engagement over attracting visitors from afar. This 10-acre park is designed to connect the historically Black Bayview-Hunters Point neighborhood to its waterfront, addressing past geographical isolation caused by traffic and barriers. The project includes renovated historic structures and new buildings that serve various community functions, such as a food pavilion and a shop for boat repair education. Future phases will enhance the park with additional amenities while continuing to foster local partnerships and accessibility for residents.